Participação de assimilados e produção de matéria seca do milho em dois sistemas de associação com feijão (Phaseolus vulgaris L.) - Cardoso, Milton José; Nogueira Fontes, Luiz Antônio; Fernandes Lopes, Nei; Domingos Galvão, José (Revista Ceres, 2025)
Growth, morphology, total dry matter accumulation and dry matter partition were studied, under field conditions, in Viçosa, Minas Gerais, using two corn-bean (Phaseolus vulgaris L.) planting systems: corn and beans in the same or alternating rows, with com planted in the spacing of 0.25; 0.50 and 1.00 m between hills, with the equivalent of four corn plants per meter.